IC 8394 Copper Hydrometallurgy - A Review And Outlook - Franklin D. Cooper (The National Institute for Occupational Safety and Health (NIOSH), 1968)
This Bureau of Mines study reviews current and proposed methods of extracting copper from sub-mill-grade ore by leaching. The amount of copper produced by hydrometallurgy has increased dramatically in recent years and will probably be about 200,000 tons per year by 1970.